Instrument Development And Assessment Of Handwriting Difficulties Among Primary School Students In Penang - Ann, Lee Sien Sut (2023)
This study explores the profile of Malay handwriting difficulties among primary school students. Malay handwriting assessment tools were used to collect the data from this targeted group. The embedded correlational mixed-method approached was employed in this study. This design embedded a qualitative component within a quantitative design. To answer the research questions, two selfdeveloped Malay handwriting assessment tools were developed to access children’s Malay handwriting performance (MyHA) and the markers related to Malay handwriting (MyHM). Both tools were developed based on an assessment tool developmental framework. Both tools went through content validity and test-retest reliability check for quality check. Data collected from the tools were used to create the profile of handwriting difficulties. 42 students from national primary schools in the Penang Island were recruited for this study using the mixed-method sampling scheme. These students (21 males and 21 females), aged between seven to twelve years were screened through MyHA and MyHM for their Malay handwriting performance and the related markers of handwriting. Proficient (n=17) and nonproficient (n=25) handwriters were identified based on the MyHA. Non-proficient handwriters were those reporting the scores of handwriting performance below the cut-off criteria.